Paintable and Rapidly Bondable Conductive Hydrogels as Therapeutic Cardiac Patches - Liang, Shuang; Zhang, Yinyu; Wang, Hongbo; Xu, Ziyang; Chen, Jingrui; Bao, Rui; Tan, Baoyu; Cui, Yuanlu; Fan, Guanwei; Wang, Wenxin; Wang, Wei; Liu, Wenguang (Advanced materials (Weinheim), 2018)
In recent years, cardiac patches have been developed for the treatment of myocardial infarction. However, the fixation approaches onto the tissue through suture or phototriggered reaction inevitably cause new tissue damage. Herein, a paintable hydrogel is constructed based on Fe3+‐triggered simultaneous polymerization of covalently linked pyrrole and dopamine in the hyperbranched chains where the in situ formed conductive polypyrrole also uniquely serves to crosslink network. This conductive and adhesive hydrogel can be conveniently painted as a patch onto the heart surface without adverse liquid leakage. The functional patch whose conductivity is equivalent to that of normal myocardium is strongly bonded to the beating heart within 4 weeks, accordingly efficiently boosting the transmission of electrophysiological signals. Eventually, the reconstruction of cardiac function and revascularization of the infarct myocardium are remarkably improved. The translatable suture‐free strategy reported in this work is promising to address the human clinical challenges in cardiac tissue engineering. A paintable conductive hydrogel is constructed based on Fe3+‐triggered polymerization of pyrrole and dopamine chemically linked to hyperbranched polymer chains. The freshly formed hydrogels can be conveniently painted as a suture‐free adhesive patch strongly bondable to the beating heart, thus efficiently boosting the reconstruction of cardiac function after myocardial infarction.